Die verkrummeling van die Augustiniaanse paradigma in die teologie? "n Kritiese bespreking van Cornelis Blom se boek Zonder grond onder de voeten - Spangenberg, IzakJ. J. (HTS teologiese studies, 2010)
The crumbling of the Augustinian paradigm of theology? A critical discussion of Cornelis Blom’s book Zonder grond onder de voeten The book Zonder grond onder de voeten (i.e. Without any foundation) is the published doctoral thesis which Cornelis Blom submitted at the Free University of Amsterdam. It focuses on evil in creation, and addresses the question: Who is responsible – God or humans? Christian theologians used to conclude (after reading Genesis 1–3) that humans are responsible. Blom, however, takes his cue from the book of Job, and comes to a totally different conclusion. According to his reading of Job and Genesis 1–4, there was no ‘fall’ from a perfect world. Evil existed right from the beginning, and God did not banish it from the world in which humans have to live. The article raises a number of questions concerning Blom’s approach, analyses and conclusions.